ANALYSIS OF THE EFFECTIVENESS OF THE FERTILIZER SUBSIDY POLICY ON RICE FARMERS IN WAJO DISTRICT - Nurbaya Busthanul; Didi Rukmana; Masyhur Syafiuddin; Mukmin Mukmin (Agrisocionomics: Jurnal Sosial Ekonomi Pertanian, 2023)
The fertilizer subsidy policy is a government program with the aim of supporting the agricultural sector by providing input subsidies through setting the highest retail price (HET) for fertilizer subsidies. The purpose of this study is to analyze the effectiveness of the fertilizer subsidy policy on rice farmers in Wajo Regency using four indicators of the effectiveness based on the fertilizer subsidy policy indicators and criteria, namely the right price, the right place, the right time, and the right amount. This study uses a survey method with a qualitative and descriptive approach. In this study, the determination of the sample used the cluster sampling with the Two-Stage Cluster Sampling in which the sampling was carried out in two stages. The data analysis method used to describe the procedure for implementing the fertilizer subsidy policy is descriptive analysis, while the data analysis method used to analyze the effectiveness of the fertilizer subsidy policy is descriptive qualitative analysis. The results of this study are the level of effectiveness of the fertilizer subsidy policy based on four indicators of overall success with an average indicator of 46.46 percent; so that it can be categorized as not effective.